Architectural Components of the Sienese Polyptych: Pictorial Illusion, Frame, and Church Space in Their Interaction - Gabovich, Valeriya M. (Actual Problems of Theory and History of Art, 2022)
The article pays attention to the triplicity of the architecture of the polyptych, namely, a comprehensive comparative analysis of the architecture of the Italian Gothic churches for which polyptychs were intended, the architecture of the frame (in cases where the original framing has been preserved, or there is visual evidence), and, finally, the pictorial illusory architecture in certain parts of polyptych, mainly in the scenes of the predella. This approach implies special attention to the architectural component of the works and their context. Thus, it becomes possible to consider the polyptych not only as an example of a style, but as an embodiment of the synthesis of arts. The article reveals that the architecture of the church, the frames, and the pictorial architecture of the polyptych do not develop synchronously: stylistic innovations characteristic of the Renaissance begin to appear earlier in the pictorial component, while in the structure of the frame, the situation changes only in the 1460s. The same applies to monumental architecture, where Gothic features were present until the second half of the 15th century due to the vividly expressed medieval tradition in Siena.
Keywords: polyptych; Siena; Quattrocento; painting; architecture